6th grade science teachers' perception and implementation of the science curriculum at a Saudi School in Kuala Lumpur / Albalawi, Anoud Mohammed H - Anoud Mohammed H, Albalawi (2020)
For decades, the Saudi Arabia government has been emphasising on education as one of the main factors for the national development. Thus, it annually improves the educational system including curriculum, training programs and school infrastructure. However, the literature argues that teachers were not involved in the decision-making and planning of educational developments which in turn affects their perception and implementation of curriculum and its objectives. This study therefore aims to explore teaching science from the teachers’ points of view of the current science curriculum. It also seeks to analyse the extent to which these teachers implement science curriculum. The study is a qualitative in nature which uses semi-structured interviews and classroom observations. It follows the theoretical frameworks of Vygotsky (1978) and Mezirow (1991) Transformative Learning Theory. The research data are collected from three science teachers who teach the sixth grade at the Saudi Schools in Kuala Lumpur, Malaysia. The findings of this study suggest that the teachers believe that the content of the current sixth grade science curriculum is informative and prescriptive in nature. It is suitable for the students’ level as well as their culture, society and religion. Moreover, teachers also perceived that the curriculum focuses towards enhancing students’ scientific skills and knowledge and relates to their daily life challenges. It is also found that teachers apply various teaching methods including discussion, lecturing and exploratory. However, teachers’ implementation is found to be partially affected by the lack of certain modern teaching tools and laboratory equipment as well as an appropriate teacher training on these tools and equipment.